Broadness and specificity: ArdB, ArdA, and Ocr against various restriction-modification systems - Kudryavtseva, Anna A.; Cséfalvay, Eva; Gnuchikh, Evgeniy Yu; Yanovskaya, Darya D.; Skutel, Mikhail A.; Isaev, Artem B.; Bazhenov, Sergey V.; Utkina, Anna A.; Manukhov, Ilya V. (Frontiers in Microbiology, 2023)
ArdB, ArdA and Ocr proteins inhibit endonuclease activity of the type I restriction-modification enzymes (RMI). In this work, we tested the ability of ArdB, ArdA and Ocr to inhibit different subtypes of Escherichia coli RMI systems (IA, IB and IC) and two Bacillus licheniformis RMI systems. In addition, the antirestriction activity of ArdA, ArdB and Ocr against a type III restriction-modification system (RMIII) EcoPI and BREX was explored. DNA mimic proteins ArdA and Ocr differ in the inhibition efficiency, and the difference depends on which RM system was tested. This effect is connected with the DNA mimicry nature. DNA-mimic protein might competitively inhibit any DNA-binding proteins; however, the efficiency of inhibition depends on the DNA-mimetic’s ability to imitate the recognition site of DNA. ArdB protein with the undescribed mechanism of action appeared to be more versatile in relation to various RMI systems and equally effectively inhibited them regardless of the recognition site. However, ArdB protein could not touch restriction systems radically different from the RMI such as BREX or RMIII. Thus, we assume that the structure of DNA mimic protein allows selective inhibition of any DNA-binding proteins depending on the recognition site. Contrariwise, ArdB-like proteins inhibit solely RMI systems independently on DNA recognition site.